Reactions of sodium tetrahydroborate with metal ions in the presence of nitrogen donor ligands - Khan, Anjum S. (My University, 1977)
The work described in this thesis is part of an ongoing effort in these laboratories to determine in more detail how a variety of factors, particularly the nature of added ligands, affects the type of products and the overall mechanism of the reactions between transition metal salts and NaBH[subscript 4]. This work specifically describes the results of the reactions between NaBH[subscript 4] and a number of II and III valent transition metal salts in the presence of the N-donor ligands ethylenediamine, 2, 2'-bipyridyl and 1, 10-phenanthroline. As well as the nature of the added ligand, variations in such factors as solvent (aqueous and ethanolic), molar ratios and rate of addition of reactants and time have also been studied. In the case of reductions of Fe, Ru and Co in the presence of phen and bipy, univalent metal complexes of general formula M(L-L)[subscript 2]BH[subscript 4]xH20 have been isolated. Reduction was also observed in the case of Cr(III) although no solids were isolated. With Zn(II) and Mn(II),~ no reduction occurred and simple hydrated metal(II)-ligand-tetrahydroborate complexes were obtained. Electrical conductivities, electronic spectra and magnetic moments on the above reduced metal complexes are reported and are consistent with the presence of the M(I) oxidation states which are unusual especially for Fe and Ru. The thesis contains a discussion of the [pi]-bonding capabilities of bipy and phen which are believed to be responsible for their ability to stabilize the metal(I) complexes.
Keywords: Borates; Transition metal compounds; Complex compounds